Methanol exchange dynamics between a temperate cropland soil and the atmosphere. (March 2018) - Bachy, A.; Aubinet, M.; Amelynck, C.; Schoon, N.; Bodson, B.; Moureaux, C.; Delaplace, P.; De Ligne, A.; Heinesch, B.
Abstract: Soil methanol (CH3 OH) exchange is often considered as several orders of magnitude smaller than plant methanol exchange. However, for some ecosystems, it is significant in regard with plant exchange and worth thus better consideration. Our study sought to gain a better understanding of soil exchange. Methanol flux was measured at the ecosystem scale on a bare agricultural soil over two contrasted periods using the disjunct eddy covariance by mass scanning technique. A proton-transfer-reaction mass spectrometer was used for the methanol ambient mixing ratio measurements. Bi-directional exchange dynamics were observed. Methanol emission occurred under dry and warm conditions and correlated best with soil surface temperature, whereas methanol uptake occurred under wet and mild conditions and correlated well with the methanol ambient concentration. After having tested a physical adsorption-desorption model and by confronting our data with the literature, we propose that the exchange was ruled by both a physical adsorption/desorption mechanism and by a methanol source, which still needs to be identified. The soil emission decreased when the vegetation developed. The reasons for the decrease still need to be determined. Overall, the dynamics observed at our site were similar to those reported by other studies for both cropland and forest ecosystems. The mechanism proposed in our work can thus be possibly applied to other sites or ecosystems. In addition, the methanol exchange rate was in the upper range of the exchange rates reported by other soil studies, suggesting that cropland soils are more important methanol exchangers than those in other ecosystems and should therefore be further investigated. Graphical abstract: Image 1 Highlights: Methanol is emitted by the soil under warm and dry conditions. Methanol is captured by the soil under wet and/or cold conditions. The exchange rates are in the upper range of those reported for soil. The presumed mechanisms were physico-chemical exchanges plus a methanol source. The soil methanol emissions decreased under the presence of plants.